2021
DOI: 10.11648/j.jps.20210905.12
|View full text |Cite
|
Sign up to set email alerts
|

Heterotic Groups, Gene Action and Heterosis Among Maize Inbred Lines Selected for the Major Agro-ecologies of Rwanda

Abstract: Maize breeding programmes exploit inbred lines with superior combining ability for grain yield and other agronomic traits to create competitive hybrids. Therefore, the objectives of this study were to determine heterotic groups of locally developed maize inbred lines, their heterotic relationships, with exotic testers as well as the gene action controlling grain yield. Nineteen maize inbred lines were crossed to four testers, based on a line x tester mating scheme resulting in 76 test crosses. These crosses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
3
5
1
Order By: Relevance
“…Therefore, hybridization and recurrent selection might be helpful for genetic enhancement of heat tolerance and superior performance under heat stress conditions [20]. The findings concur with several authors [17,19,22,[36][37][38] who reported significant GCA and SCA for grain yield under heat-stressed and optimal conditions. The significant GCA f and GCA m effects observed for grain yield under managed heat stress and optimal conditions imply that both parents contributed to the inheritance of grain yield in the hybrids under these conditions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, hybridization and recurrent selection might be helpful for genetic enhancement of heat tolerance and superior performance under heat stress conditions [20]. The findings concur with several authors [17,19,22,[36][37][38] who reported significant GCA and SCA for grain yield under heat-stressed and optimal conditions. The significant GCA f and GCA m effects observed for grain yield under managed heat stress and optimal conditions imply that both parents contributed to the inheritance of grain yield in the hybrids under these conditions.…”
Section: Discussionsupporting
confidence: 89%
“…The differences in heritability values for grain yield observed under stress, optimal conditions, and across environments were in line with the reports of several researchers [11,22,47]. The higher value of broad-sense heritability for yield, under heat stress, optimal conditions, and across environments suggests that environmental effects had a small role in the variation observed [48].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…On contrary Riboniesa et al [14] classified 21 inbred lines using single tester and assigned 11 inbred lines in to two heterotic groups. Alphonse Nyombayire et al [15] classified 3 maize inbred lines (S4, S6 and S7) that were considered as testers discriminated the seven local lines into three heterotic groups. Elmyhun et al [16] Positive heterosis for kernel yield were reported by Ali et al [17] and Mideksa et al [18].The testers were able to classify 15 out of 27 inbred lines into heterotic groups A, B, and AB based on SCA effects presented in (Table 6).…”
Section: Classifying Inbred Lines Into Heterotic Groupsmentioning
confidence: 99%
“…Most of the authors reported combining ability and heterosis studies in normal corn (Amegbor et al, 2020;Bisen et al, 2020;Elmyhun et al, 2020;Gramaje et al, 2020;Kamara et al, 2020;Keimeso et al, 2020;Khamphasan et al, 2020;Onejeme et al, 2020;Patil et al, 2020;Scaria., 2020;Upreti et al, 2020;Yu et al, 2020;Abdulazeez et al, 2021;Maphumulo et al, 2021;Nyombayire et al, 2021;Riacheet al, 2021) and very few authors ( Dermail et al, 2020;Ravikesavan et al, 2020;Vanipraveena et al, 2021) pertaining to sweet corn. Keeping up with the demand of sweet corn in the market, development of sweet corn hybrids is need of the hour.…”
Section: Identification Of Promising Parental Lines and Hybridsmentioning
confidence: 99%